DETERMINAN FAKTOR PENGUKURAN KINERJA BANK KONVENSIONAL TAHUN 2015 – 2019 - M Hendri Yan Nyale; Fransisca Amalia Sari Manurung (JURNAL LENTERA BISNIS, 2024)
This study has purposed to determine the effect of CAR, BOPO, NPL, NIM and LDR on ROA in the Public Banking Industry on the Indonesia Stock Exchange for the 2015-2019 period. The hypothesis test of this study using Multiple Linear Regression Analysis. The sampling method used purposive sampling method, using certain criteria. The sample population are 30 banks that have foreign exchange transactions from 44 conventional banks listed on the Indonesia Stock Exchange. The results show that CAR has a positive and significant effect on ROA, BOPO has a negative and significant effect on ROA, NPL has a negative and significant effect on ROA, NIM has a negative and significant effect on ROA, LDR has a negative and significant effect on ROA. Keyword: CAR, BOPO, NPL, NIM, and ROA